Vocabulary Learning Strategies Employed by Indonesian Virtual Exchange Students - Utomo, Dias Tiara Putri; Ahsanah, Finaty; Islami, Arum; Suratmi, Suratmi; Suhariyati, Suhariyati (Jurnal Ilmu Pendidikan, 2022)
This study investigated the types of vocabulary learning strategies (VLS) employed by Indonesian college students. The study specifically aimed to find out (a) the most and the least frequently used VLS, and (b) the most useful VLS. A total of 105 nursing students who attended a virtual exchange program during the odd semester of 2021/2022 academic year participated in this study. This was ex post facto research which used a vocabulary learning strategy questionnaire to collect the data. To answer research questions, the collected data were analyzed by using SPSS statistics 25.0, including the descriptive statistics. The overall findings revealed that in terms of five categories, determination strategies were reported to be the most frequently used strategies and social strategies were the least ones. In terms of individual strategies, the most frequently used vocabulary learning strategies were ‘using bilingual dictionaries either print or electronic’, ‘guessing word meaning through the context’, and ‘learning new vocabulary items through vocabulary videos”. The least frequent ones were ‘asking the word’s synonym to the teacher’ and ‘communicating with native speakers. Furthermore, the participants assumed that ‘using bilingual dictionaries either print or electronic’ and ‘taking notes of new words’ as the most useful strategies. Considering the results, both students and lecturers must be more aware of the effective learning strategies to achieve better results